The evolution of meteorology : a look into the past, present, and future of weather forecasting - Teague, Kevin Anthony, 1985- 4 16; 1988- Gallicchio, Nicole; 5 Ohio Library and Information Network (Hoboken, NJ : Wiley Blackwell, 2017)
The essential guide to the history, current trends, and the future of meteorology This comprehensive review explores the evolution of the field of meteorology, from its infancy in 3000 bc, through the birth of fresh ideas and the naming of the field as a science, to the technology boom, to today. The Evolution of Meteorology reveals the full story of where meteorology was then to where it is now, where the field is heading, and what needs to be done to get the field to levels never before imagined. Authored by experts of the topic, this book includes information on forecasting technologies, organizations, governmental agencies, and world cooperative projects. The authors explore the ancient history of the first attempts to understand and predict weather and examine the influence of the very early birth of television, computers, and technologies that are useful to meteorology. This modern-day examination of meteorology is filled with compelling research, statistics, future paths, ideas, and suggestions. This vital resource: Examines current information on climate change and recent extreme weather events ; Starts with the Ancient Babylonians and ends with the largest global agreement of any kind with the Paris Agreement ; Includes current information on the most authoritative research in the field of meteorology ; Contains data on climate change theories and understanding, as well as extreme weather statistics and histories ; This enlightening text explores in full the history of the study of meteorology in order to bring awareness to the overall path and future prospects of meteorology--Provided by publisher.
Building blocks of meteorology (3000 BC -1950 AD). Ancient civilizations, philosophical theories, and folklore (3000 BC -1400 AD) -- Inventions of weather instruments (1400-1800) -- Birth of modern meteorology (1800-1950) -- The early television, computer, satellite, and radar era (1950-1980). Television and the first computerized advancements -- Radar and satellite history -- Modern day technologies, advancements, and social media impacts (1980-2013). Personal technology boom -- Covering major storms -- The rise of modern computer models -- Advancements within the nationalized governmental weather departments -- Meteorological agencies : globally to the private sector -- Current and future ideologies of climate change and meteorological processes. Climate change -- Extreme weather -- Additional meteorological impacts -- The future and direction of meteorology. Weather technology -- Global cooperation.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; History.;History. -- Meteorology;Weather forecasting -- 2; 20; Electronic books.;History.